THU0472 Factors associated with readiness for adopting osteoporosis treatment change. (12th June 2018) - Danila, M.I.; Rahn, E.J.; Mudano, A.S.; Outman, R.C.; Li, P.; Redden, D.T.; Anderson, F.A.; Greenspan, S.L.; LaCroix, A.Z.; Nieves, J.W.; Silverman, S.L.; Siris, E.S.; et al.
Abstract : Background: Understanding factors associated with the readiness for adopting osteoporosis treatment change may inform the design of behavioural interventions to improve osteoporosis treatment uptake in women at high risk for fracture. Objectives: To examine the factors associated with the readiness for adopting osteoporosis treament change among US women with prior fractures. Methods: US women in the Global Longitudinal Study of Osteoporosis (GLOW) with prior self-reported fractures who were not currently using osteoporosis therapy were eligible to participate in the Activating Patients at Risk for OsteoPOroSis (APROPOS) Study. Participants' readiness for behaviour change was assessed using a modified form of the Weinstein Precaution Adoption Process Model (PAPM). We defined pre-contemplative participants as those who self-classified in the unaware and unengaged stages of PAPM. Contemplative participants were defined by the undecided, decided not to act, and decided to act stages of PAPM. Bivariate tests and stepwise multivariable logistic regression evaluated the following factors associated with these two levels of readiness for behaviour change: sociodemographic characteristics, health literacy, self-reported history of depression and dementia, previous treatment for osteoporosis, whether participants had been told they had osteoporosis/osteopenia, and whether they had concerns about osteoporosis. Results: A total of 2684 women were enrolled in APROPOS. Participants were 95% Caucasian, with a mean (SD) age 74.9 (8.0) years and 77% had some college education. Overall, 25% (n=544) self-classified in the contemplative stage of behaviour change. Compared to women who self-classified as pre-contemplative, contemplative women were more likely to be concerned about osteoporosis (adjusted OR [aOR]=3.2, 95% CI 2.3–4.4) and to report prior osteoporosis treatment (aOR 4.3, 95% CI 3.1–6.0). Participants who were told they had osteoporosis had a 12.4 fold odds to be in the contemplative group (95% CI 8.5–18.1), while those who were told they had osteopenia had 4.1 fold odds to be in the contemplative group (95% CI 2.9–5.9). Conclusions: Among women with high risk of future fracture, having been told by a health care provider that they had osteoporosis/osteopenia was independently associated with considering taking medications for osteoporosis. Our results suggest that in considering osteoporosis intervention design efficiency and effectiveness, women's recognition of a diagnosis of osteoporosis/osteopenia are critical components to be considered when attempting to influence stage of behaviour transitions. Disclosure of Interest: M. I. Danila: None declared, E. Rahn: None declared, A. Mudano: None declared, R. Outman: None declared, P. Li: None declared, D. Redden: None declared, F. Anderson Grant/research support from: Portola, Consultant for: Millennium Pharmaceuticals, S. Greenspan Grant/research support from: Amgen, Lilly, Consultant for: Merck, A. LaCroix Consultant for: Amgen, Pfizer, Sermonix, J. Nieves: None declared, S. Silverman Grant/research support from: Amgen, Lilly, Consultant for: Amgen, Speakers bureau: Amgen, Lilly, E. Siris Consultant for: Amgen, Radius, N. Watts Shareholder of: OsteoDynamics, Grant/research support from: Shire, Consultant for: AbbVie, Amgen, Janssen, Merck, Radius, Sanofi, Paid instructor for: Amgen, Shire, S. Ladores: None declared, K. Meneses: None declared, J. Curtis Grant/research support from: Amgen, Consultant for: Amgen, K. Saag Grant/research support from: Amgen, Lilly, Merck, Consultant for: Amgen, Lilly, Merck